The Malay Rulers: Their Position and Article 38(4) - Wan Ahmad Fauzi, Wan Husain (ISTAC-IIUM Publications & Abad Sinergi Sdn Bhd., 2025)
MALAYSIA is a monarchy that safeguards constitutional supremacy. Despite their prominent status in the nation, the role of the Malay Rulers remains a topic of scholarly inquiry and public discourse. Their involvement in defining the rule of law is crucial, especially in addressing modern constitutional challenges. The evolving landscape of Malaysian society, shaped by exposure to foreign doctrines, political conflicts, and religious diversity, presents new challenges for the Malay Rulers and the Conference of Rulers at the federal level. Understanding their constitutional roles and responsibilities requires a right interpretation of their existence, position, and influence in the nation’s governance.